The Use of Multimedia Material of Teaching Modern Mathematics - Layous, Mohammad Kaisb (2011)
The world today is witnessing acceleration in all areas of science and knowledge, and the explosion of the third revolution, the so-called technological revolution. And the emergence of a new era the era of electronics and communications, led to obvious changes in all aspects of daily life. It will need to be on education systems to respond to these events, and attempt to put the principles and criteria for the selection of teaching methods appropriate for the renewal of education, and create a learning environment. The modern education must be compatible with changes that occur, where they can develop cognitive abilities and skills of the learner, which are difficult to develop by the traditional education system. This is what made us think in a new way of teaching mathematics to ninth grade in middle school in Iraq and the use of information technology and communications. The many students lack imagination, cognition, perception and analysis. The need working in this research on the use of information and communication technology through the design of the system contains the multimedia and interactive games designed to support the educational process and to overcome the difficulties faced by students. In addition to make mathematics from the world of rigid into a world full of movement and creativity. Where the design of this application by using a special methodology supports multimedia called Multimedia Designs and Planning Pyramid (MUDPY). That contributed to the provide requirements of the user (Teacher \ Student) very well, where they were to reach these results through data collection and process of the questionnaire to the user, after the tested the system and evaluated by the user (Teacher \ Student). This has given great support to this study and makes them take a new dimension in the educational process, where it has borne the idea of expanding this experience and use in other sciences.